The Social and Educational action of Young People in the October Demonstration: An anthropological Study in Al-Tahrir Square, Baghdad - Ahmed, Mohamed Jamil (Al-Adab Journal, 2022)
Iraqi society has gone through great and tremendous developments in political and party work, especially after 2003, when the political arena witnessed the presence of more than three hundred political parties competing among themselves in most parts of the Iraqi state, and that this large number of parties did not present their obligations towards the people especially since most of them had their electoral programs filled with promises and achievements, of which nothing was actually achieved except rarely. And this reality has produced great popular anger, especially in the current stage, which witnessed the growth of the spirit and patriotic sense among the youth of the necessity of the uprising against these politicians and changing them because they failed to achieve the people’s ambition. This feeling resulted in the Great October Demonstration, which coincided on October 25. 2019, which pervaded the entire cities of Iraq especially in Al-Tahrir Square, where all segments of society were present, expressing their categorical rejection of the presence of political parties and the need to change them, declaring a set of goals. The most important of which are amending the constitution, providing services, changing the government, exposing the corrupt and restoring the prestige of the state. This situation continued for a long time and with great momentum and strength until this demonstration, led by the rebellious youth, succeeded in achieving part of its demands to change the government and announce early elections. The study seeks to achieve a set of goals. The most important of which are to reveal the nature and reality of the October Demonstration and its reflection in Iraqi society and to identify the most important negatives and positives in the arenas of demonstrations and to identify the most important problems faced by the youth of the October Demonstration, especially in the demonstration squares and the disclosure of the basic demands of the popular protests against the government, and the importance of the study revolves around two aspects: the first of which is theoretical, which focuses on the concepts of study and literature, anthropology and social studies, which have taken care of the situation. The second is the field aspect in which the study seeks to apply anthropological approaches and tools such as interviews and observation by participation in order to reach accurate scientific results that serve scientific research.